Catalytic Oxidative Desulfurization of Dibenzothiophene Utilizing Composite Based Zn/Al Layered Double Hydroxide - Nur Ahmad; Erni Salasia Fitri; Afan Wijaya; Amri Amri; Mardiyanto Mardiyanto; Idha Royani; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
In this study, the Zn/Al-TiO2 and Zn/Al-ZnO was successfully synthesized. The catalysts were characterized by X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), and Scanning Electron Microscope—Energy Dispersive X-ray Spectroscopy (SEM-EDS). The typical diffraction peaks of Zn/Al-LDH, TiO2, and ZnO still appear in the Zn/Al-TiO2 and Zn/Al-ZnO composites, indicating that the composite preparation did not change the form of precursors. FTIR spectra of Zn/Al-TiO2 and Zn/Al-ZnO showed absorption band at 3448, 1627, 1381, 832, 779, and 686 cm-1. The catalysts have an irregular structure where the percent mass of Ti and Zn on the composite at 10.6% and 55.6%, respectively. The acidity of Zn/Al-LDH composite increased after being composed with TiO2 and ZnO. The percentage conversion dibenzothiophene on Zn/Al-ZnO, Zn/Al-TiO2, ZnO, Zn/Al-LDH, and TiO2 was 99.38%, 96.01%, 95.36%, 94.71%, and 91.92%, respectively. The heterogeneous systems of catalytic reaction was used for reusability. After 3 cycles catalytic reactions at 50 oC for 30 min, the percentage conversion of dibenzothiophene on Zn/Al-LDH, TiO2, ZnO, Zn/Al-TiO2, and Zn/Al-ZnO were 77.42%, 83.19%, 82.34%, 84.91%, and 89.71 %, respectively. The composites of Zn/Al-TiO2 and Zn/Al-ZnO have better reusability test than Zn/Al-LDH, TiO2, and ZnO, which proofing that Zn/Al-TiO2 and Zn/Al-ZnO have a stable structure. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).